The Agile Project Management Mapping Research - Fang, Aiwen (2015)
Purpose: This dissertation reviews the agile project management (APM) related literatures to identify its academic current scenarios. Furthermore, this dissertation also discovers the future research directions of agile project management, especially its application in non-software related industries.